Acute toxicity and genotoxicity studies on new melatonergic antidepressant GW117. Issue 3 (March 2023) - Gao, Mei; Ma, Hui; Liu, Tianbin; Cao, Chong; Zheng, Zhiyong; Tang, Liansheng; Gu, Wei; Zhang, Daizhou; Sun, Haiji
Abstract: GW117, a novel derivate compound of agomelatine that acts as both a 5-HT2C receptor antagonist and a MT1/MT2 receptor agonist, likely underlines the potent antidepressant action with less hepatotoxicity than agomelatine. We evaluated the acute toxicity of GW117, and the genotoxicity of GW117 using bacterial reverse mutation test, mammalian chromosomal aberration test in Chinese hamster lung cells (CHL) and mouse bone marrow micronucleus test. The acute toxicity test results showed that maximum tolerated dose (MTD) of GW117 was 2000 mg/kg, under which mean Cmax and AUC0→t was 10, 782 ng/mL and 81, 046 ng/mL × h, respectively. The result of bacterial reverse mutation test showed that the number of bacterial colonies in each dose group of GW117 did not increase significantly compared with that in the solvent control group with or without S9 metabolic activation system. In vitro chromosome aberration test of CHL cells, the chromosome aberration rate of each dose group of GW117 did not increase with or without S9 metabolic activation system. In mouse micronucleus test, the highest dose was 2000 mg/kg, the micronucleus rate did not increase significantly. Under the conditions of this study, the MTD of a single GW117 administration was 2000 mg/kg, there was no genotoxicity effect of GW117. Highlights: The MTD of a single GW117 administration to SD rats was 2000 mg/kg, under which mean Cmax and AUC0 .→t was 10, 782 ng/mL and 81, 046 ng/mL × h, respectively. Ames test was negative induced by GW117 at 0.15625 mg/plate-5 mg/plate. In vitro mammalian chromosome aberration test was negative induced by GW117. Mouse micronucleus test was negative induced by GW117 at 250 mg/kg～2000 mg/kg.